Where have all the workers gone? Employment termination in East Germany after unification - Georg Licht; Viktor Steiner (Zentrum für Europäische Wirtschaftsforschung (ZEW); ZBW – Leibniz Information Centre for Economics, 1992)
Employment termination in East Germany in the first nine months after unification is analyzed within a discrete hazard rate model with three absorbing states, namely short-time work, unemployment and non-participation. Estimation is based on a cohort of employed individuals in June 1990 and the calendar data in the second wave of the German Socio-Economic Panel (East). The time-dependency (duration dependence) of these rates is described by a flexible specification of the' baseline hazard function. The effects of personal characteristics, education and occupation, wages, firm characteristics as well as industry and region on both the transition rates into the three states and the survival rate in employment are analyzed.
Keywords: 330